2020
DOI: 10.1111/dth.13929
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cytology in oral ulcer and comparison with histopathology and direct immunofluorescence

Abstract: Rapid diagnosis of pemphigus vulgaris (PV) is an important task in patient's prognosis and treatment. Although PV is routinely diagnosed through investigation of pathology specimens and direct immunofluorescence assays, Tzanck smear can be used as rapid, inexpensive, and easily used test to confirm its clinical diagnosis. This study aimed to determine the diagnostic value of Tzanck smear in erosive oral lesions of PV and also determine its sensitivity and specificity for diagnostic purposes. A total of 68 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is suggested that the lack of deep cell collection could be a possible differentiating factor. Regarding the incidence of acantholytic cells, 80.5% (33/41) of the oral erosive lesions in PV cases were found to be acantholytic, while in the control group, Lichen planus, the incidence was 0% (0/12) in H&E‐stained smears and 18.1% (2/11) in Giemsa‐stained smears 2 . The sensitivity of acantholytic cells in Tzanck smear of erosive oral lesions of PV cases was 80.5% (for both Giemsa and H&E staining), whereas specificity values of Giemsa and H&E staining were 84.6% and 96.3%, respectively 2 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is suggested that the lack of deep cell collection could be a possible differentiating factor. Regarding the incidence of acantholytic cells, 80.5% (33/41) of the oral erosive lesions in PV cases were found to be acantholytic, while in the control group, Lichen planus, the incidence was 0% (0/12) in H&E‐stained smears and 18.1% (2/11) in Giemsa‐stained smears 2 . The sensitivity of acantholytic cells in Tzanck smear of erosive oral lesions of PV cases was 80.5% (for both Giemsa and H&E staining), whereas specificity values of Giemsa and H&E staining were 84.6% and 96.3%, respectively 2 .…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the incidence of acantholytic cells, 80.5% (33/41) of the oral erosive lesions in PV cases were found to be acantholytic, while in the control group, Lichen planus, the incidence was 0% (0/12) in H&E‐stained smears and 18.1% (2/11) in Giemsa‐stained smears 2 . The sensitivity of acantholytic cells in Tzanck smear of erosive oral lesions of PV cases was 80.5% (for both Giemsa and H&E staining), whereas specificity values of Giemsa and H&E staining were 84.6% and 96.3%, respectively 2 . However, Papanicolaou stain is usually used for cytological evaluation in oral mucosal diseases because it is useful in differentiating squamous cell lesions due to its color tone that reflects the degree of squamous cell differentiation, and we used Papanicolaou stain again for this evaluation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although histopathology and direct immunofluorescence are the gold standard for pemphigus group of disorders, Tzanck smear is a cost-effective tool in resource-poor settings, with a sensitivity of 80.5% and specificity of 84.6% for oral pemphigus. 1 However, the standard procedure in dermatology literature involves scraping the erosion with the blunt end of a surgical blade, often causing patient apprehension, pain, and bleeding. Moreover, lesions on the posterior part of buccal mucosa or palate are inaccessible by this method (Supplementary Fig 1, available via Mendeley at https://data.mendeley.com/datasets/ks2gwtckh3/1 ).…”
Section: Challengementioning
confidence: 99%